Analisis Kelayakan Finansial dan Strategi Pengembangan Pembibitan Mangrove di Desa Percut, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang - Rijal F Banjarnahor; Agus Purwoko; Yunasfi Yunasfi (Peronema Forestry Science Journal, 2013)
The aim of this research were to know the process and tecnique of mangrove nursery, the level of financial feasibility of mangrove nursery and to knew the development strategy of mangrove nursery business. The method of data collecting of this research was interview and observation. The evaluation of financial analysis was done by production cost and revenue analysis. Then was followed by analysis of R/C ratio and Break Event Poin (BEP), and the development strategy analysis was used SWOT analysis. The result show that the techniques of nursery was done by tradisional way. The nursery stage area: selection of place, nursery place, fruit selection, manufacture of seedlings and maintenance of seedling. The business of mangrove nursery feasible to run due to the R/C ratio more than one. The R/C ratio for R. Stylosa, R. Apiculata, Soneratia, Bruguiera sp. Were 1,2642, R. Mucronata was 2,4737 and A. Marina was 1,1939. Based on the SWOT analysis, the current position of the mangrove nursery rides was in quadrant III. It showed that business of mangrove nursery was many threat, but had a great opportunity to develop. Keywords: Mangrove, nursery, financial analysis, SWOT